Lipid-Based Nanosystems for the Topical Application of Ferulic Acid: A Comparative Study - Maddalena Sguizzato; Francesca Ferrara; Markus Drechsler; Anna Baldisserotto; Leda Montesi; Stefano Manfredini; Giuseppe Valacchi; Rita Cortesi (MDPI AG, 2023)
In this study, we examined and compared two different lipid-based nanosystems (LBNs), namely Transferosomes (TFs) and Monoolein Aqueous Dispersions (MADs), as delivery systems for the topical application of Ferulic Acid (FA), an antioxidant molecule derived from natural sources. Our results, as demonstrated through Franz-cell experiments, indicate that the LBNs produced with poloxamer 188 in their composition create a multilamellar system. This system effectively controls the release of the drug. Nonetheless, we found that the type of non-ionic surfactant can impact the drug release rate. Regarding FA diffusion from the MAD, this showed a lower diffusion rate compared with the TF. In terms of an in vivo application, patch tests revealed that all LBN formulations tested were safe when applied under occlusive conditions for 48 h. Additionally, human skin biopsies were used to determine whether FA-containing formulations could influence skin tissue morphology or provide protection against O3 exposure. Analyses suggest that treatment with TFs composed of poloxamer 188 and MAD formulations might protect against structural skin damage (as observed in hematoxylin/eosin staining) and the development of an oxidative environment (as indicated by 4-hyroxinonenal (4HNE) expression levels) induced by O3 exposure. In contrast, formulations without the active ingredient did not offer protection against the detrimental effects of O3 exposure.Inizio modulo.